(3GdYhdeI GdEbJUGOjI (B/s - (3Nda, adjM MSfs ((3GQHO(B: s (3YGde GdcJH GdMOjK(B, s, 2009)
(3eGgjI GdYhdeI GdGbJUGOjI , YhdeI GdGShGb , YhdeI GdGSJKeGQ, YhdeI GdGfJGL , YhdeI GdJLGQI , GdYhdeI GdeGdjI , GdJcfhdhLjG h GdYhdeI GdGbJUGOjI , YhdeI GdHMK GdYdej h GdJWhjQ GdJcfhdhLj , eDSSGJ GdYhdeI GdGbJUGOjI , GdYhdeI GdGbJUGOjI h GdOhd GdeJbOeI h GdOhd GdfGejI , SdHjGJ GdYhdeI GdGbJUGOjI , GjLGHjGJ GdYhdeI GdGbJUGOjI h GaGbgG , GdGReGJ GdGbJUGOjI h GdYhdeI GdGbJUGOjI (B.s
(3eQGLY U(B.421s
Keywords: (3GdGbJUGO GdOhdjs; (3GdGbJUGO GdYGdejs; (3GdEbJUGO(B- (3GdYhdeIs